Human Resource Management Strategies to Enhance Employee Productivity at Perum Bulog, Makassar Branch Office - Hikma. B; Asriati; Ismail Rasulong (LP2M IAIN Palopo, 2026)
This study aims to analyze human resource management (HRM) implementation, identify factors inhibiting HRM effectiveness, and formulate appropriate strategies to improve employee productivity at Perum BULOG Makassar Branch Office. The study employed a qualitative descriptive approach using interviews, observation, and documentation as data collection methods. Informants consisted of branch management and employees directly involved in HRM and operational activities. Data were analyzed using SWOT analysis integrated with the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), and TOWS Matrix. The findings indicate that HRM at Perum BULOG Makassar Branch Office has been implemented relatively systematically through workforce planning, recruitment, employee placement, training, performance appraisal, coaching, and managerial support. However, several inhibiting factors remain, including workload imbalances, limited employee availability during periods of high operational demand, unequal access to training, competency gaps in adapting to digital systems, and suboptimal coordination and communication. The IFAS analysis produced a strength score of 3.648 and a weakness score of 2.427, while the EFAS analysis generated an opportunity score of 3.672 and a threat score of 3.267. The resulting strategic coordinates of (1.221; 0.405) place the organization in Quadrant I, indicating an aggressive strategy. Therefore, the recommended strategy is SO, emphasizing continuous competency development, technology utilization, improved workload allocation, stronger coordination, and optimization of work systems. This study contributes a contextual HRM strategy framework for state-owned food and logistics enterprises.